2020
DOI: 10.21203/rs.3.rs-37240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lactate Albumin Ratio is Associated with Mortality in Patients with Moderate to Severe Traumatic Brain Injury

Abstract: Abstract Background: Traumatic brain injury (TBI) is a serious public health issue all over the world. This study was designed to evaluate the prognostic value of lactate to albumin ratio (LAR) on moderate to severe traumatic brain injury.Methods: Clinical data of 273 moderate to severe TBI patients hospitalized in West China Hospital between May 2015 and January 2018 were collected. Multivariate logistic regression analyses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our results are in line with multiple studies looking at the importance of the L/A ratio in several conditions such as: sepsis (prospective study including 155 patients), heart failure (retrospective study including 4562 patients) and traumatic brain injury (retrospective study involving 273 patients). They found that the L/A ratio was a good predictor of mortality [ 16–18 ]. However, these studies were either retrospective in nature [ 16 , 18 ] or limited by their sample size [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with multiple studies looking at the importance of the L/A ratio in several conditions such as: sepsis (prospective study including 155 patients), heart failure (retrospective study including 4562 patients) and traumatic brain injury (retrospective study involving 273 patients). They found that the L/A ratio was a good predictor of mortality [ 16–18 ]. However, these studies were either retrospective in nature [ 16 , 18 ] or limited by their sample size [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the L/A ratio was a good predictor of mortality [ 16–18 ]. However, these studies were either retrospective in nature [ 16 , 18 ] or limited by their sample size [ 17 ]. The largest retrospective study was done by Gharipour et al.…”
Section: Discussionmentioning
confidence: 99%